2011
DOI: 10.1111/j.1365-294x.2011.05282.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses and disruptive effects: how major wildfire influences kinship‐based social interactions in a forest marsupial

Abstract: Environmental disturbance is predicted to play a key role in the evolution of animal social behaviour. This is because disturbance affects key factors underlying social systems, such as demography, resource availability and genetic structure. However, because natural disturbances are unpredictable there is little information on their effects on social behaviour in wild populations. Here, we investigated how a major wildfire affected cooperation (sharing of hollow trees) by a hollow-dependent marsupial. We base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
(133 reference statements)
1
20
0
Order By: Relevance
“…Even within the same study region (and species), different studies have revealed contradictory patterns in different populations. Mountain brushtail possums at Cambarville (within the broader region studied here) shared dens less often and used fewer trees where hollow trees were scarce [15], [23], [46]. These results contradict the present findings and are consistent with predictions from theoretical and empirical work suggesting that resource defence behaviour and intolerance of other individuals develops under resource competition [30].…”
Section: Discussionsupporting
confidence: 68%
“…Even within the same study region (and species), different studies have revealed contradictory patterns in different populations. Mountain brushtail possums at Cambarville (within the broader region studied here) shared dens less often and used fewer trees where hollow trees were scarce [15], [23], [46]. These results contradict the present findings and are consistent with predictions from theoretical and empirical work suggesting that resource defence behaviour and intolerance of other individuals develops under resource competition [30].…”
Section: Discussionsupporting
confidence: 68%
“…) or fire (Banks et al . ). Differences in spatial genetic structure between two locations may simply be capturing points in which temporal variation differs; variation in dispersal patterns is not necessarily synchronous between sites.…”
Section: Discussionmentioning
confidence: 97%
“…dispersal) must be fine‐tuned to local constraints and immediate opportunities (Arnaud et al. 2012; Banks et al. 2012; Blyton et al.…”
Section: Kin Competitionmentioning
confidence: 99%